PROFIL INTUISI SISWA KELAS IX SMP NEGERI 3 SALATIGA DALAM MEMECAHKAN MASALAH KESEBANGUNAN DITINJAU DARI KECERDASAN MATEMATIS-LOGIS, KECERDASAN LINGUISTIK, DAN KECERDASAN VISUAL SPASIAL - Pratiwi, Rani; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to describe intuition profile of ninth grade students of SMP Negeri 3 Salatiga in similarity problem solving reviewed from mathematical-logical intelligence, linguistic intelligence, and visual spatial intelligence. The research was a qualitative research. The subjects of the research were taken by using purposive sampling. The subjects of the research were ninth grade students of SMP Negeri 3 Salatiga odd semester of academic year 2015/2016. Data collection techniques used is a task-based interviews, while the validity of the data using a time triangulation technique. The instrument of this study was consists of two, researchers as the main instrument that supported by multiple intelligences questionnaire, problem solving tests, and interview guidelines. Data analysis technique includes three activities, those are data reduction, data presentation, and conclusion. Data analysis was performed based on intuition category indicators in problem solving. Based on the results of data analysis showed that the intuition profile of ninth grade students of SMP Negeri 3 Salatiga in similarity problem solving is as follows: (1) Students with mathematical-logical intelligence use affirmatory intuition in understanding the problems and planning solutions, but do not use intuition when doing settlement plan, while in checking answer, students use conclusive intuition, (2) students with linguistic intelligence use affirmatory intuition, but do not use intuition when doing settlement plan of the students, while in checking answer, students do not use intuition conclusive, (3) students with visual spatial intelligence use anticipatory intuition in understanding the problems and planning solutions, but do not use intuition when doing settlement plan, while in checking answer, students use conclusive intuition.Key words: intuition profile, similarity, logical-mathematical intelligence, linguistic intelligence, visual spatial intelligence